1985
DOI: 10.1111/j.1469-8137.1985.tb02875.x
|View full text |Cite
|
Sign up to set email alerts
|

RELATIVE CHANGES IN LEVELS OF POLYAMINES AND ACTIVITIES OF THEIR BIOSYNTHETIC ENZYMES IN BARLEY INFECTED WITH THE POWDERY MILDEW FUNGUS, ERYSIPHE GRAMINIS D.C. ex MERAT f.sp. HORDEI MARCHAL

Abstract: SUMMARYThe concentrations of three amines (putrescine, spernaidine and spermine) were much increased in first leaves of barley infected with powdery mildew, whilst the concentrations of putrescine and spermidine in roots of mildewed barley were significantly decreased. Although no significant change in the activities of three polyamine biosynthetic enzymes (ADC, arginine decarboxylase; ODC, ornithine decarboxylase; and SAMDC, S-adenosyl methionine decarboxylase) could be detected in roots of mildewed barley, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 21 publications
2
22
0
Order By: Relevance
“…Root ODC activity was enhanced by mycelia inoculation and is consistent with changes in polyamine biosynthesis enzyme activities observed by Waiters et al (1985) upon fungal infection of barley leaves. As the ODC assay includes root and fungal sources, work should continue in pure roots, perhaps monitoring ODC in conjunction with other biochemical techniques such as arginine decarboxylase (ADC) found in significant levels in roots (Altman et al, 1982).…”
Section: Discussionsupporting
confidence: 59%
“…Root ODC activity was enhanced by mycelia inoculation and is consistent with changes in polyamine biosynthesis enzyme activities observed by Waiters et al (1985) upon fungal infection of barley leaves. As the ODC assay includes root and fungal sources, work should continue in pure roots, perhaps monitoring ODC in conjunction with other biochemical techniques such as arginine decarboxylase (ADC) found in significant levels in roots (Altman et al, 1982).…”
Section: Discussionsupporting
confidence: 59%
“…Only a few reports have appeared about host-fungi interactions. Infection of barley with two fungi (Puccinia hordei [24] or Erysiphe graminis [36]) resulted in large increases in polyamine content which seemed to be the result of the release from preexisting conjugate forms in the green islands in diseased tissues (35). However, Bakanasvili et al (2) found that infection of tomato fruits by Rhizopus stolonifer or their treatment with ethylene resulted in decreases in polyamine content.…”
Section: Discussionmentioning
confidence: 96%
“…Studies conducted so far in relation with the role of PAs in plant-pathogen interactions have focused mainly on viruses (Negrel et al, 1984;Bellés et al, 1991;Torrigiani et al, 1997;Yamakawa et al, 1998;Hiraga et al, 2000;Marini et al, 2001;Yoda et al, 2003;Yoo et al, 2004) and biotrophic fungi causing rusts and mildews on several different hosts (Walters et al, 1985;Walters and Wylie, 1986;Cowley and Walters, 2002). However, the attention previously devoted to the effects of necrotrophic plant pathogens on host PA metabolism has been very scant (Angelini et al, 1993;Rea et al, 2002).…”
Section: Changes In Pa Metabolism Of Tobacco Plants Infected By the Nmentioning
confidence: 99%